2020
DOI: 10.21203/rs.3.rs-33445/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meta-analysis of genome-wide association study identifies FBN2 as a novel locus associated with Systemic Lupus Erythematosus in Thai population

Abstract: Background: Differences in the expression of variants across ethnic groups in the Systemic Lupus Erythematosus (SLE) patients have been well documented. However, the genetic architecture in the Thai population has not been thoroughly examined. In this study, we carried out genome-wide association study (GWAS) in the Thai population. Methods: Two GWAS cohorts were independently collected and genotyped: discovery dataset (487 SLE cases and 1,606 healthy controls) and replication dataset (405 SLE cases and 1,590 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…GWAS data on Chinese populations were retrieved from our previous studies derived from Hong Kong, Guangzhou, Central China, and Jining populations (7,15), comprising 4,734 cases and 9,425 controls (7,15). The Thai GWAS was obtained from a recent study (9) and was reanalyzed to be consistent with the processes of imputation and quality control for the European and Chinese GWAS (7), resulting in a total of 835 cases and 2,995 controls. Sample information for each cohort is summarized in Supplementary Table 1, on the Arthritis & Rheumatology website at https://onlinelibrary.wiley.com/doi/10.1002/art.42021.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…GWAS data on Chinese populations were retrieved from our previous studies derived from Hong Kong, Guangzhou, Central China, and Jining populations (7,15), comprising 4,734 cases and 9,425 controls (7,15). The Thai GWAS was obtained from a recent study (9) and was reanalyzed to be consistent with the processes of imputation and quality control for the European and Chinese GWAS (7), resulting in a total of 835 cases and 2,995 controls. Sample information for each cohort is summarized in Supplementary Table 1, on the Arthritis & Rheumatology website at https://onlinelibrary.wiley.com/doi/10.1002/art.42021.…”
Section: Methodsmentioning
confidence: 99%
“…We further demonstrated that the ancestral genetic differences affected transferability of polygenic risk scores (PRS) among different populations (7). Additionally, in a study focusing on a Thai SLE cohort, we have shown that the FBN2 locus was associated with SLE in the Thai population but not in either Chinese or European populations (9). Consistent with studies on other complex diseases (10–12), multi‐ancestral genome‐wide association studies (GWAS) in SLE have proven to be valuable in detecting genetic factors that underlie ancestral differences.…”
Section: Introductionmentioning
confidence: 99%
“…The GWAS summary statistics of the multi-ancestry and multi-trait SLE meta-analysis result have been deposited on the Shiny App [https:// liugroupstatgen.shinyapps.io/SLEv] for users to download and interactively explore research results. This meta-analysis result was derived via MTAG 30 and METAL 88 from the following datasets: SLE 11,[16][17][18][19][20][21][22][23]108 , ATD 22 , CD 109,110 , CEL 111,112 , MS [112][113][114] , PBC 115,116 , RA 22,117 , SJO 22,118 , SSC 119 , T1D 22,120 , and VIT 121 . We also obtained GWAS data from FinnGen Release 5 website [https://www.finngen.fi/en/access_results], Pan-UK Biobank website [https://pan.ukbb.broadinstitute.org], and BioBank Japan PheWeb [https://pheweb.jp] for traits available in these biobanks.…”
Section: Software Urlsmentioning
confidence: 99%
“…Previous SLE GWAS results were primarily from individuals of European ancestry [16][17][18][19] . Fortunately, several recent GWAS efforts have greatly increased the sample size of non-European ancestry including East Asians 11,[20][21][22][23] .…”
mentioning
confidence: 99%